2016
DOI: 10.1002/hed.24406
|View full text |Cite
|
Sign up to set email alerts
|

Tumor infiltrating lymphocytes and survival in patients with head and neck squamous cell carcinoma

Abstract: Because immune responses within the tumor microenvironment may be important predictors of tumor biology, correlations of specific types of tumor infiltrating lymphocytes (TILs) with clinical variables and outcomes were determined in 278 previously untreated patients with head and neck cancer (HNSCC). Methods Infiltrating levels of CD4 (helper T cells), CD8 (cytotoxic/suppressor T cells), FoxP3, regulatory T cells), CD68 (myeloid derived suppressor cells) and CD1a (Langerhan) cells were retrospectively measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
291
1
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 293 publications
(315 citation statements)
references
References 47 publications
20
291
1
3
Order By: Relevance
“…46 We observed that high levels of transcripts from one or any combination of two genes expressing immune checkpoint molecules (PD1, TIM3, TIGIT, LAG3) in HPV+, but not HPV-, HNSCC can predict patient survival after surgery. These findings require confirmation by prospective clinical studies to–we anticipate–pave the way for the development of immune-predictive biomarkers for HPV+ HNSCC patients that will ultimately lead to treatment deintensification in this patient population.…”
Section: Discussionmentioning
confidence: 81%
“…46 We observed that high levels of transcripts from one or any combination of two genes expressing immune checkpoint molecules (PD1, TIM3, TIGIT, LAG3) in HPV+, but not HPV-, HNSCC can predict patient survival after surgery. These findings require confirmation by prospective clinical studies to–we anticipate–pave the way for the development of immune-predictive biomarkers for HPV+ HNSCC patients that will ultimately lead to treatment deintensification in this patient population.…”
Section: Discussionmentioning
confidence: 81%
“…Several studies have reported that the LC number is increased in the leukoplakia lesions of patients with smoking habits and in oral squamous cell carcinomas [17,18]. Similarly, HPV infection modulates the tumor immune environment as demonstrated by Nguyen et al, who reported that the number of LCs (CD1a-positive cells) is reduced in the stroma of younger oropharyngeal cancer patients with HPV infection [19].…”
Section: Introductionmentioning
confidence: 83%
“…75 A population of CD68-positive immature myeloid cells (called myeloid-derived suppressor cells (MDSCs) that inhibit proliferation and cytokine release by T cells was found to be present in glioma 76 and squamous cell carcinoma tumors. 77 These cells can be produced by the tumor microenvironment from circulating monocytes. 78 TAMs, MDCDs, and other tumor-associated immune cells compose the leukocytic infiltrate, of which TAMs are the major contributors.…”
Section: Cd68 In Cancermentioning
confidence: 99%